Lombok’s Tsunami and Stock Abnormal Returns - Suryani, Ani Wilujeng; Pertiwi, Karina Dian (Accounting Analysis Journal, 2021)
Natural disaster often brings damage to the economy, including the decrease of stock’s market value. For this reason, this study aims to determine the effect of the tsunami earthquakes in Lombok in 2018 on abnormal returns and cumulative abnormal returns of insurance companies. This study used the event study approach, with three days window period after the three tsunami earthquakes from July to August 2018. The sample of this study is the stock price of 14 insurance companies listed on the Indonesia Stock Exchange. To test whether abnormal return exists, a one-sample t-test was used on the average abnormal and cumulative returns. The results show that the tsunami earthquake disasters in Lombok in 2018 have a significant effect on cumulative abnormal returns of insurance companies stocks, and this effect even bigger on the third tsunami. This finding shows that the market reacts to continuous disaster by considering the earthquake as negative information and thus decrease the stock price. This study implies that investors may buy the stocks after the disaster to get a cheaper price or hold the stocks to avoid loss. Keywords: abnormal return; event study; Lombok tsunami earthquake; signaling theory